Developing Geotourism as Part of Sustainable Development at Ciletuh Sukabumi, West Java, Indonesia - YULIAWATI, Ayu Krishna; SAPARI DWI HADIAN, Mohamad; RAHAYU, Agus; HURRIYATI, Ratih (Journal of Environmental Management and Tourism, 2016)
Indonesia is a country rich with natural and cultural resources, which have the potential to be developed, further the tourism sector. Indonesia has 3 world heritages, 50 national parks and 7 geoparks in Indonesia. Geopark is a form of sustainable development with a new paradigm in managing resources. The Geopark concept in Indonesia is the development of a region based on a sustainable manner that combines three diversities, namely: geodiversity, biodiversity, and cultural diversity. Sukabumi is located at West Java Province, Indonesia where there is Geopark Ciletuh as a new tourism destination. The area has geosites with the oldest rock formation in the region; fossils, water fall and natural amphitheater. Tourism has brought concerns regarding issues such as biodiversity conservation, waste management, and water supply. The study objectives are to explore how geotourism can contribute to the region sustainable development, and what the implications are there for Geopark stakeholders. Qualitative method (desk study also field survey) and descriptive analysis was used in the study. The study found exploitation of natural resources in the area that can threaten tourism activity also sustainable development and weakness in the regional policy for development that focus mainly on regional growth but fails to include preservation of the built environment.
Keywords: geotourism; sustainable development